The Implementation of Akhaff Al-Ḍararayn Principle in Marriage Dispensation Decisions at The Religious Court - Afnan Zumrotul Habib Farhani; Saifullah Saifullah; Abid Rohmanu (Institut Agama Islam Negeri Ponorogo, 2026)
Background/Introduction: Marriage dispensation is a legal policy that provides leniency for couples who have not yet reached the minimum legal age for marriage, yet its implementation creates legal and social dilemmas. This condition is important to examine, particularly regarding the application of the akhaff al-ḍararayn principle in judges’ considerations at the Ponorogo Religious Court. Research Objectives: This study aims to examine the application of the akhaff al-ḍararayn principle in marriage dispensation decisions and the implementation of Supreme Court Regulation (PERMA) Number 5 of 2019 concerning Guidelines for Adjudicating Marriage Dispensation Applications. Methodology: This study employed a library research method with a normative juridical approach through the analysis of official court documents in the form of judges’ decisions related to marriage dispensation cases at the Ponorogo Religious Court. Results: The findings indicate that in Decision Number 241/Pdt.P/2023/PA.Po, the judge granted the marriage dispensation application because it was considered the lesser harm. In contrast, in Decision Number 416/Pdt.P/2021/PA.Po, the judge rejected the application because rejection was deemed the lesser harm. Both decisions were consistent with the akhaff al-ḍararayn principle and implemented PERMA Number 5 of 2019 both procedurally and substantively. Unique Contribution: This study demonstrates the relevance of the akhaff al-ḍararayn fiqh principle in modern judicial practice concerning marriage dispensation cases. Conclusion: Judges’ considerations in marriage dispensation cases are oriented toward public benefit (maslahah) and the prevention of greater harm. Recommendations: Future studies are recommended to examine more marriage dispensation decisions from various regions.